Establishment and Application of Rapid Detection Method for Polymyxin Resistance Gene mcr-1 Based on RPA-LFD Method - Xue JIAO; Yuzhi DONG; Jingwen WANG; Chenze LÜ; Jiehong FANG; Han JIANG (Shipin gongye ke-ji, 2023)
Objective: To develop a rapid, efficient and visual method for the detection of bacterial colistin resistance gene mcr-1, so as to provide the basis and convenience for the development of its detection at the grassroots level. Methods: Using recombinase polymerase amplification combined with a lateral flow dipstick (RPA-LFD) assay, supplemented by a hand-held colloidal gold reader. According to the conserved sequence of the mcr-1 gene, a pair of specific RPA primers were designed and synthesized. Through the optimization of the reaction conditions and system, as well as the specificity test, sensitivity test, simulated food sample test and actual sample test, the RPA-LFD assay for visual and quantitative detection of bacterial colistin resistance gene mcr-1 was successfully established. Results: When the primer concentration was 400 nmol/L and the primer ratio was 1:1, the optimal reaction conditions of this method are Mg2+ concentration 14.0 mmol/L, reaction temperature 37 ℃ and reaction time 20 min. The sensitivity was good, the standard curve equation was y=0.117x+0.051, the quantification limit was 101~108 copies/μL, and the detection limit was 101 copies/μL, which was an order of magnitude lower than the PCR method and the detection result of the simulated sample was consistent with the PCR method. Carrying status of colistin resistance gene mcr-1 in each 15 pork samples, chicken samples, pig farm environmental samples, broiler farm environmental samples, Escherichia coli isolates and Enterobacter campylobacter isolates were analyzed by the established RPA-LFD assay. The detection rate of positive samples by RPA-LFD assay was consistent with that of conventional PCR method, and a total of 9 mcr-1 gene positive samples were detected. RPA-LFD quantitative analysis showed that the concentration of mcr-1 gene in positive samples was between 4.5×102~8.6×104 copies/µL. Conclition: The RPA-LFD detection method of the bacterial colistin resistance gene mcr-1 established in this study had strong specificity, high sensitivity, and simple operation, and could be widely used in grassroots inspections.